Kindergarten and School Social Assistance During the COVID-19 Pandemic in Hungary (Papers in Arts and Humanities, 2021)
In this paper, we have analyzed the results obtained in the third year of our longitudinal research (2018–2020) regarding the work of kindergarten and school social workers, research conducted in connection with the Hungarian Educational Research Association. The service provided by kindergarten and school social workers was made generally available in Hungary by a legislation change implemented in 2018. By the end of the school year 2018/2019, after initial difficulties, we noticed a positive change in the supportive attitude and acceptance of teachers and public educational institutions towards the work of kindergarten and school social workers. We confirmed an increase in connections to fellow professions as well as in the level of mutual initiative (Homoki & Czinderi, 2020). The continuous development of the service and the reinforcement of professionals is essential as there is a high degree of fluctuation at the national level (Sinka, 2019), even more increased by the effects of the COVID-19 pandemic, posing unprecedented challenges for actors in public educational institutions. Based on our qualitative data obtained by a focus group interview, we have shown how social workers in different types of settlements and educational institutions of the country (N = 13) were ableto adapt to the crisis. What was the degree of fluctuation? What kind of challenges did they face, and what types of resources were they able to mobilize during the online education in the first and second waves of the pandemic? Our data show a shift in priorities at the individual, group, and community levels of social work.
Keywords: kindergarten and school social workers; online education; pandemic; professional resources; flexibility